Urban Agriculture: A way forward to augment Food and Nutritional Security in cities - G.R. Desai,; N. Balasubramani, (Journal of Agricultural Extension Management, 2025)
The process of urbanisation is fast spreading across different countries. and regions to which India is no exception. Migration to urban areas is increasing to access the facilities and improved level of living. This process has resulted in emergence of many issues such as demand for food, employment, income generation, safe disposal of urban waste etc. in urban areas. Since provision of food and nutritional security of the population in urban areas is a top priority it is felt necessary to introduce urban agriculture as a development strategy to address the requirement partially. The present study examines the profile of urban population, the pattern of purchase and consumption and level of satisfaction with two major commodities like vegetables and milk. The study highlights the need to promote urban agriculture as a development strategy.